CARICOM : appropriate adaptation to a changing global environment (Ian Randle KingstonJM, 2005)
Presents analyses of aspects of ongoing negotiations, as well as reform proposals and adjustment processes to which CARICOM countries have been, and will be subjected to for the forseeable future. Looks at options facing the countries in respect of role as commodity producers(especially of bananas and sugar); the possibility of a novel approach to delimitation of the interlocking exclusive economic zone (EEZ) in the Caribbean; and renewal of the agenda of political integration.
Keywords: CARICOM